Mandates for managing water resources in mega urban region: case study for Selangor - Siti Zuhaili Hasan,; Sarah Aziz Abdul Ghani Aziz, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2017)
The need to manage water resources that transverses traditional administrative boundaries and legislative jurisdiction require a rethink in determining mandates, particularly in mega urban region. Malaysia practices a federated system of government, whereby the Federal Constitution of Malaysia 1957 sets out the legislative and executive remit for both Federal and State Government. Water resources in this case falls within the legislative remit of the State Government. The state of Selangor is unique as it is a mega urban region in its own right and plays host to two federated territories, with rivers coursing through them. It is also unique because it forms the bulk of the area identified as the Greater Kuala Lumpur Region earmarked for economic and social development. Both the Federated Territories of Kuala Lumpur and Putrajaya sit in the middle of Selangor state with rivers coursing through them beginning and ending in Selangor. This study briefly looks at the mandates required to balance the prerequisites of managing water resources that transverses boundaries. It will look at how the state of Selangor can manage the resources through its Lembaga Urus Air Selangor Enactment 1999 to fulfil the proposed objectives of the National Water Resources Policy 2012.